Dynamics Of The Community In The Implementation Of Complete Systematic Land Registration Program In The Land Office Of Blora Regency - Nuryanto Nuryanto; Umar Ma'ruf (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2020)
The birth of a complete systematic land registration program is expected to reduce the level of land problems faced by the government, especially in fulfilling land rights and accelerating the making of land certificates for the community. In this research, the formulation of the problem proposed is how is the dynamics of the community in implementing a complete systematic land registration in Blora Regency?. This study uses a sociological juridical approach to the type of analytical descriptive research. The data used for this study are primary and secondary data taken by library research methods, field research, and interviews. Based on the results of the study concluded that the dynamics of the community towards the implementation of the PTSL program by looking at the benefits of the program which has a great influence on the welfare of the community. In an effort to realize the welfare of the community, the community receiving land certificates through PTSL can be mobilized together to make various productive businesses that are expected to improve the community's economy.Keywords: Community Dynamics; Complete Systematic Land Registration; Land Office.